Answer:The f(x) takes the place of the y-axis
The F in f(x) stands for the functions name.
The X in f(x) stands for the ordered pair.
The f(x) is the same as Y= 2x - 1
Step-by-step: f(x) = 2x - 1
F(x) = F(13)
F(13) = 2*13-1=26-1=25
2*13=26 26-1=25
so the answer to f(x)=2x-1 would be 25 because the x in f(x) is a 13 and you would multiply the 2 by 13 and that would equal 26 then you would minus 1 and the answer would be 25
Step-by-step explanation:
Function notation is the way a function is written. It is meant to be a precise way of giving information about the function without a rather lengthy written explanation.The f (x) notation is another way of representing the y-value in a function, y = f (x). The y-axis may even be labeled as the f (x) axis, when graphing. Ordered pairs may be written as (x, f (x)), instead of (x, y).
I hope this is correct and if it is I hope it helps.